2020
DOI: 10.1016/j.molmet.2020.101097
|View full text |Cite
|
Sign up to set email alerts
|

Moderate SIRT1 overexpression protects against brown adipose tissue inflammation

Abstract: Objective Metainflammation is a chronic low-grade inflammatory state induced by obesity and associated comorbidities, including peripheral insulin resistance. Brown adipose tissue (BAT), a therapeutic target against obesity, is an insulin target tissue sensitive to inflammation. Therefore, it is necessary to find strategies to protect BAT against the effects of inflammation in energy balance. In this study, we explored the impact of moderate sirtuin 1 (SIRT1) overexpression on insulin sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
(143 reference statements)
2
14
0
Order By: Relevance
“…HSL phosphorylation) and the lipolytic response as visualized by the higher size of the lipid droplets in brown adipocytes receiving CM-Lps and CL316243 compared to the controls. As expected from the impaired β-adrenergic signaling, Ppargc1a mRNA and UCP1 protein levels were significantly reduced in agreement with data in C3H10T1/2 (10T1/2) mouse mesenchymal stem cells [ 72 ] and our recent study [ 36 ]. Of relevance, herein we show that, in brown adipocytes, ectopic expression of HIF1α is sufficient to suppress their responses to CL316243.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HSL phosphorylation) and the lipolytic response as visualized by the higher size of the lipid droplets in brown adipocytes receiving CM-Lps and CL316243 compared to the controls. As expected from the impaired β-adrenergic signaling, Ppargc1a mRNA and UCP1 protein levels were significantly reduced in agreement with data in C3H10T1/2 (10T1/2) mouse mesenchymal stem cells [ 72 ] and our recent study [ 36 ]. Of relevance, herein we show that, in brown adipocytes, ectopic expression of HIF1α is sufficient to suppress their responses to CL316243.…”
Section: Discussionsupporting
confidence: 92%
“…Generation of brown preadipocyte cell lines and differentiation. Brown preadipocytes were isolated from the interscapular BAT of 20-day old suckling mice and immortalized as previously described [ 36 ]. Brown preadipocytes were also immortalized from Ampkα1 −/− mice [ 37 ] or mice containing loxP-flanked alleles of HIF1α previously described [ 38 ], referred as BA Ampkα1−/- and BA Hif1afl/fl , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the impact of inflammation on BAT activity is currently discussed, as some studies in mice with obesity-associated chronic low-level inflammation reported that BAT inflammation is associated with decreased thermogenic activity ( Sakamoto et al, 2016 ; Escalona-Garrido et al, 2020 ), in other studies no correlation between BAT thermogenesis and inflammation was observed ( Cao et al, 2018 ; Boulet et al, 2021 ). To the best of our knowledge, the in vivo effects of acute inflammation mediated by CLP-induced sepsis in expression of BAT thermogenic- and metabolic-related genes have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was done as described by Escalona-Garrido and colleagues 58 . Paraffin sections were heated for 20 min in 100 mM sodium citric buffer (pH 6.0) and 0.05% Tween-20 and then blocked for 10 min with a solution of 9% H 2 O 2 in 10% methanol.…”
Section: Methodsmentioning
confidence: 99%